Comparison of Quantitative and Qualitative (Q)SAR Models Created for the Prediction of Ki and IC50 Values of Antitarget Inhibitors - Lagunin, Alexey A.; Romanova, Maria A.; Zadorozhny, Anton D.; Kurilenko, Natalia S.; Shilov, Boris V.; Pogodin, Pavel V.; Ivanov, Sergey M.; Filimonov, Dmitry A.; Poroikov, Vladimir V. (Frontiers in Pharmacology, 2018)
Estimation of interaction of drug-like compounds with antitargets is important for the assessment of possible toxic effects during drug development. Publicly available online databases provide data on the experimental results of chemical interactions with antitargets, which can be used for the creation of (Q)SAR models. The structures and experimental Ki and IC50 values for compounds tested on the inhibition of 30 antitargets from the ChEMBL 20 database were used. Data sets with Ki and IC50 values including more than 100 compounds were created for each antitarget. The (Q)SAR models were created by GUSAR software using quantitative neighbourhoods of atoms (QNA), multilevel neighbourhoods of atoms (MNA) descriptors and self-consistent regression. The accuracy of (Q)SAR models was validated by the 5-fold cross-validation procedure. The balanced accuracy was higher for qualitative SAR models (0.80 and 0.81 for Ki and IC50 values, respectively) than for quantitative QSAR models (0.73 and 0.76 for Ki and IC50 values, respectively). In most cases sensitivity was higher for SAR models than for QSAR models, but specificity was higher for QSAR models. The mean R2 and RMSE were 0.64 and 0.77 for Ki values and 0.59 and 0.73 for IC50 values, respectively. The number of compounds falling within the applicability domain was higher for SAR models than for the test sets.